2017
DOI: 10.1016/j.cie.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Shop floor lot-sizing and scheduling with a two-stage stochastic programming model considering uncertain demand and workforce efficiency

Abstract: Efficient and flexible production planning is necessary for the manufacturing industry to stay competitive in today's global market. Shop floor lot-sizing and scheduling is one of the most challenging and rewarding subjects for the management. In this study, a two-stage stochastic programming model is proposed to solve a single-machine, multi-product shop floor lot-sizing and scheduling problem. Two sources of uncertainties are considered simultaneously: product demand from the market, and workforce efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
4
0
4
Order By: Relevance
“…From them, release/due-date based objective functions represent only the 4%, lot-sizing 5%, and costing 4% of the publications, advising that these essential objective functions are under-presented, needing more profound attention. This fact has been underlined in particular in [1,45,66].…”
Section: A Quantitative Analysis Of the Literaturementioning
confidence: 96%
“…From them, release/due-date based objective functions represent only the 4%, lot-sizing 5%, and costing 4% of the publications, advising that these essential objective functions are under-presented, needing more profound attention. This fact has been underlined in particular in [1,45,66].…”
Section: A Quantitative Analysis Of the Literaturementioning
confidence: 96%
“…The results showed that the approaches were able to obtain solutions compatible with the reality of the production process under study. In [20][21][22], uncertainties are addressed in the production process with stochastic models outperforming deterministic ones. The optimal value of the optimization model was properly approximated when using an enough number of scenarios in the stochastic approach.…”
Section: Related Workmentioning
confidence: 99%
“…O tratamento da incerteza em processos produtivos é um desafio que tem sido tratado na literatura através da proposição de modelos e métodos estocásticos HU, 2016;LI;HU, 2017). Todavia, o presente trabalho busca endereçar tal desafio através de uma abordagem que permite alocar o risco incorrido no processo de tomada de decisão para planejamento e sequenciamento da produção.…”
Section: Desafios E Objetivosunclassified
“…Como mencionado, os autores em (TANG; CHE; LIU, 2012; ALEM; MORABITO, 2015) abordam técnicas de modelagem estocástica para tratar o processo de produção em indústrias considerando contextos reais. Vários autores na literatura, tais como (HU; HU, 2016;LI;HU, 2017;ALEM et al, 2018), abordam incertezas no processo de produção. Todavia, até onde foi pesquisado na condução deste projeto, não há na literatura estudos mais aprofundados com tratamentos de incertezas em ambientes que lidam com o processo de preparação da soja para extração de óleo.…”
Section: Processos De Laminaçãounclassified
See 1 more Smart Citation